The impact of foreign-direct investment on economic growth in Malaysia: the role of financial development - Alzaidy, Ghaith; Niaz Ahmad, Mohd Naseem; Lacheheb, Zakaria (EconJournals, 2017)
This paper investigates the impact of foreign-direct investment (FDI) and financial development on economic growth in Malaysia over the period of 1975-2014. According to autoregressive distributed lag bound test approach to co integration analyses, the results found that financial development plays an essential role in mediating the impact of FDI on economic growth in Malaysia. This implies that well-developed financial sectors lead to further and facilitate FDI spill over and hence yield economic growth, particularly for the case of Malaysia.